Hepatotoxicity induced by antituberculosis drugs among patients coinfected with HIV and tuberculosis Hepatotoxicidade das drogas antituberculose entre pacientes coinfectados HIV/tuberculose - Maria de Fátima Silva de Lima; Heloísa Ramos Lacerda de Melo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
Hepatotoxicity due to antituberculosis drugs limits treatment in patients coinfected with HIV and tuberculosis. We conducted a case-control study to identify risk factors for hepatotoxicity among patients coinfected with tuberculosis and HIV in two hospitals in Recife, Pernambuco State, Brazil. The sample consisted of 57 patients (36.5% of the total) who developed hepatotoxicity and a control group of 99 patients (63.5% of the total), who did not present this effect. Hepatotoxicity consisted of jaundice or a high concentration of AST/ALT or total bilirubinemia. Multivariate logistic regression showed that a T CD4+ count of < 200cells/mm³ increased the risk of hepatotoxicity by a factor of 1.233 (p < 0.001) and that coinfection with hepatitis B or C virus increased this risk by a factor of 18.187 (p = 0.029). Discharge occurred among 66.1% of the case group (p = 0.026). The absence of hepatotoxicity was a protective factor against death (OR = 0.42; 95%CI: 0.20-0.91). Coinfection with the B and C hepatitis virus and a T CD4+ cell count below 200cells/mm³ were independent risk factors for hepatotoxicity in these patients Hepatotoxicidade secundária às drogas antituberculose limita o tratamento em pacientes coinfectados com HIV e tuberculose. Conduzimos estudo caso-controle para identificar fatores de risco para hepatotoxicidade entre pacientes com tuberculose e infecção pelo HIV em dois hospitais de Recife, Pernambuco, Brasil. O grupo caso consistiu de 57 (36,5%) pacientes com hepatotoxicidade e o grupo controle, 99 (63,5%) pacientes que não a apresentaram. Hepatotoxicidade foi definida como icterícia ou alta concentração de ALT/AST ou de bilirrubinemia total. Regressão logística multivariada mostrou que a contagem de linfócitos T CD4+ < 200 células/mm³ aumentou o risco de hepatotoxicidade em 1,233 vezes (p < 0,001), e coinfecão com vírus de hepatite B ou C aumentou o risco em 18,187 (p = 0,029). Alta hospitalar ocorreu em 66,1% dos pacientes do grupo caso (p = 0,026). Ausência de hepatotoxicidade foi fator de proteção para óbito (OR = 0,42; IC: 0,20-0,91). Coinfecção pelos vírus das hepatites B e C e linfócitos T CD4+ abaixo de 200 células/mm³ foram fatores de risco independentes para a hepatotoxicidade nesses pacientes.